2017
DOI: 10.1108/imds-11-2016-0472
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging social network sites for new product launch

Abstract: Purpose -The ability to make use of social network sites (SNSs) to promote new products and facilitate positive word of mouth around new product launch (NPL) presents an important opportunity. However, the mechanisms and motivations of SNS users are not well understood and businesses frequently fail to realize these opportunities. This paper examines some of the forces that motivate people to spend time on SNS sites and how these motivations are related with people's propensity to engage in behaviours that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…Understanding what motivates virtual community members and drives behaviours is seen as vital (Roberts, et al, 2017), in order to understand and influence activities such as co-creation (Candi, et al, 2018;Marion, et al, 2016) and WtP. Mathwick (2002) divides behaviours into exchangeoriented and communally-oriented social norms.…”
Section: Motivationmentioning
confidence: 99%
“…Understanding what motivates virtual community members and drives behaviours is seen as vital (Roberts, et al, 2017), in order to understand and influence activities such as co-creation (Candi, et al, 2018;Marion, et al, 2016) and WtP. Mathwick (2002) divides behaviours into exchangeoriented and communally-oriented social norms.…”
Section: Motivationmentioning
confidence: 99%
“…Also, this is the phase where consumers come in contact with the final product for the first time and share their experiences, concerns, feedback, like/dislike with other customers and with the firm. Despite being one of the critical stages in the new product development process, research in the area of new product launch is infantile [19], [34].…”
Section: Social Media and The Launch Phase Of New Productmentioning
confidence: 99%
“…Few studies also highlight the important role social media can play in the process of new product development (NPD) [17], [18]. However, the past literature offers a limited number of studies which focuses on the use of social media for the launch or commercialization of new product [19]. The present study aims to bridge this gap and introduces popular categories of social media platforms available in the launch phase of NPD.…”
Section: Introductionmentioning
confidence: 97%
“…The proliferation of social media platforms has enabled entrepreneurs to better connect with their customers and to engage them in the development of new products and product launches. For example, Aral and Dellarocas (2013) and Roberts et al (2017) have indicated this fact. The IoT is often used to sell products, automate workflows and engage with consumers (Valacich and Schneider 2018).…”
Section: Introductionmentioning
confidence: 95%